Traditional Views and Attitude Toward Waste and Rivers in Indonesia: Challenges of Cleaning Up the Indonesia Polluted Enviroment - Suwarno Peter (EDP Sciences, 2021)
Since water is an indispensable part of humanity, human communities settle near water sources, and one of the most popular water sources is a river. In the past millennial, around 80% of Javanese communities were located near rivers. However, traditional views, attitudes, and behavior during the development and urbanization era and lack of political will have compromised sustainable uses of rivers choked with pollution from industrial and neighborhood wastes. This paper will discuss the stories of pollution and waste management that have led to Indonesia being one of the most polluted nations by looking at traditional socio-cultural views of waste and rivers and efforts to deal with the problems of garbage. This study is mainly based on various data from previous research, NGO and government programs, and interviews with local community members and leaders. In addition to the challenges of garbage disposal and cleaning up Indonesian rivers, this study will conclude with suggestions on how to change people’s attitudes and behavior and government programs to create long-term sustainable and participative waste management efforts in Indonesia.